Pengaruh Non Performing Financing Terhadap Profitabilitas Bank Umum Syariah Periode 2018-2021 - Muhammad Dimas Prasetyo; Djoni Djatnika; Kristianingsih Kristianingsih (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This study aims to analyze the effect of NPF (Non Performing Financing) on profitability with the ratio of NPM (Net Profit Margin) of Islamic Commercial Banks in Indonesia, either partially or simultaneously. The NPF used is the NPF mudharabah, NPF musyarakah, and NPF murabahah. The research conducted is a quantitative research using secondary data obtained from Islamic Banking Statistics 2018-2021 which has been carried out to the public through the official website of the Financial Services Authority. The sample was selected by purposive sampling technique so that the selected sample was Islamic Commercial Banks in Indonesia. The data analysis method used in this research is multiple linear regression analysis method. The hypothesis test that will be used is the t test to partially test the hypothesis and the F test to test the hypothesis simultaneously. The results showed that partially the mudharabah NPF had a significant effect on the profitability of Islamic commercial banks in a positive direction, while the musyarakah NPF and murabahah NPF partially had no effect on the profitability of Islamic commercial banks. Simultaneously, NPF mudharabah, NPF musyarakah, and NPF murabahah have no effect on the profitability of Islamic Commercial Banks.